The oblique view cardiology from a different angle - Norell, Michael S. (Tfm Pub., 2007)
How do common cardiac drugs get their name? What sort of music do surgeons choose to listen to as they delve amongst our innards? Why can going to cardiac conferences be so damned irritating and how close to reality are all those TV hospital dramas? This book features a collection of musings that touch on these and other aspects of cardiology.